Green economic development and entrepreneurship transformation - Aleksy Kwilinski; Oleksii Lyulyov; Tetyana Pimonenko (Entrepreneurial Business and Economics Review (EBER), 2024)
Objective: The article aims to analyse the role of entrepreneurship transformation in attaining green economic development among EU countries for the 2007-2022 period. Research Design & Methods: This study applied the following methods to check the hypothesis of the study: the Malmquist‒Luenberger productivity index for measuring green economic development; fully modified ordinary least squares (FMOLS) and dynamic ordinary least squares (DOLS), systems and first-difference generalized method of moments (GMM) - to check the entrepreneurship transformation effect on green economic development. Findings: The findings of the study demonstrate a strong positive correlation between green economic development and the transformation of entrepreneurship, highlighting the crucial link between economic prosperity and initiatives in the green economy. The analysis confirms that historical changes in productivity related to green economic practices have a positive effect on future developments. Furthermore, the significant coefficients for green economic development emphasize the enduring nature of green economic practices. Implications & Recommendations: The empirical results allowed us to outline the following suggestions: 1) government policies should focus on initial investments in green practices, incentivizing businesses through financial mechanisms and robust regulations to foster economic and environmental sustainability; 2) enhancing green economic development requires simplifying the process for creating new businesses, particularly green startups, and offering financial and procedural support to inject innovation and economic vitality into the sector; 3) trade openness is crucial for boosting green economy productivity, necessitating policies that lower trade barriers while incorporating environmental standards to ensure sustainable growth; 4) fostering innovation in environmental technologies with increased government funding and strategic partnerships between academia, industry, and government needed to propel sustainable economic transformation. Contribution & Value Added: The value added by this article lies in its empirical grounding and practical implications, which guide policymakers regarding the importance of supporting entrepreneurial initiatives to drive green economic development. It suggests targeted government policies that incentivize the adoption of green practices, simplify processes for new green startups, promote trade openness, and foster innovation through increased funding and collaboration.
Keywords: L26; Q01; Q5; 330; sustainable development; business; green growth; green business; innovation